Alterações mamográficas em mulheres que vivem com HIV-aids - Mendes, Mônica Bannwart [UNESP] (2015)
Background: Despite viral replication control, the chronic use of antiretroviral drugs leads to several changes in HIV carriers, among which are lipodystrophy and premature aging. The objectives were to evaluate mammographic density in women older than 35 years living with HIV/AIDS and relate breast density to age, time of exposure to antiretroviral therapy (cART), CD4 + T lymphocyte count, HIV viral load and the presence of lipodystrophy with incidence of breast fatty replacement (BFR). Methods: Observational cohort of women divided into two groups: G1, comprising 59 HIV-infected individuals and G2, consisting of 73 uninfected women, all aged 35 to 72 years. The following variables were studied: age at the moment of the interview, at menarche, at the last pregnancy and at menopause; use of hormones; breast pain; previous history of breast surgery and family history of breast or ovarian cancer. Results: BFR differences were observed between the groups when they were analyzed by age ranges, from 35 to 40 years (p=0.002) and from 41 to 45 years (p=0.041), with a higher proportion in G1 and in G2 at the age ranges of 51 to 55 years (p=0.046) and 56 to 60 years (p=0.005). The chance of lipodystrophy was 9.3- fold greater after 10 years of cART use, and it occurred in 29 (49.2%) women in G1. Conclusions: women with HIV/AIDS showed BFR at earlier ages when compared to uninfected women, and no relation to the number of pregnancies, lipodystrophy, having AIDS or asymptomatic infection or CD4 + T lymphocyte count was found